RESOLUSI KONFLIK ANTAR ETNIS KABUPATEN LAMPUNG SELATAN (STUDI KASUS: KONFLIK SUKU BALI DESA BALINURAGA DAN SUKU LAMPUNG DESA AGOM KABUPATEN LAMPUNG SELATAN) - Anisa Utami; Puji Astuti; Turtiantoro . (Journal of Politic and Government Studies, 2014)
Deversity often becomes the bases for an  individual or a group to be involved into conflict vertically as well as horizontally due to the idiological or ethnic differences and the difference in perspective between one another. These differences become very fundamental in a conflict. In Indonesia, the country in many different forms ranging from religious to ethnic differences is highly vulnerable to different horizontal conflict. This study uses a qualitative research method which is descriptive in nature, which means that the most important research instrument is the researcher herself. While the object of the study is in accordance with the formulation of the problems that have been described and is focused on parties to the conflict, that is, Agom and Balinuraga villagers, and also the elites in the villages as well as the South Lampung regency administration. One of the ethnic conflicts in Indonesia is an ethnic conflict between Balinese ethnic which is settled in Balinuraga village and Lampungnese ethnic which is settled in Agom village. The two ethnic groups occupy the same territory that is in the South Lampung regency. Small conflicts grew to the largest conflict in October 2012 and resulted in loss of life. The violent conflict that took place on 27 October - 29 October 2012 as the accumulation of small conflicts that often occurred between the two ethnic groups in the study leads to a question, that is, what is really the root cause of the ethnic conflict in South Lampung regency and what efforts are taken by the government as the conflict resolution mediator. The most dominant factor in the cause of inter-ethnic conflict in South Lampung regency after doing research in the field is the lack of space interaction between different ethnic societis. Historical factors when ethnic Balinese society first arrived as transmigration in South Lampung district and placed in an uninhabited area and no native settlements ethnic makes Balinese people a very exclusive and does not mingle with the natives and other ethnicities in the district of South Lampung. South Lampung regency administration has tried well to solve the conflict by acting as a conflict mediator between ethnic Bali and Lampung. Therefore, the Local Government with indigenous organizations that have been formed as MPAL (Assembly of high Indigenous people of Lampung) and FKDM (Forum Early Awareness Society) implements development on an ongoing basis so that the interaction between inter-ethnic keeps running in South Lampung regency and goes well to eliminate prejudice from each ethnic.Keywords: Resolution, Ethnic Conflict, Mediator